Islamic Education Students’ Perceptions: A Phenomenological Study on the Ethical of Using Artificial Intelligence (AI) in Learning - Rahman, Muhammad Rezza Nur; Afandi, Nur Kholik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The use of Artificial Intelligence or AI in learning as a form of integration between real and virtual world in the Society 5.0 Era presents challenges in the ethical aspect, such as forms of responsibility for use, data security issues, and plagiarism in the creation of works. The concept of ethical use of AI in learning is needed, included in the perception of Islamic Religious Education students as AI users in Islamic Education learning, will provide a broader perspective and could be associated with the context of Islamic Education. This research will explore the perception of Islamic Education (PAI) students about the ethics of using AI in learning based on phenomena at Islamic State University of Sultan Aji Muhammad Idris (UINSI) Samarinda. Descriptive qualitative research with phenomenological methods is used to answer the formulated objectives. Data collection uses interview techniques supported by surveys. Data analysis using the Miles, Huberman, and Saldaña models in the form of data condensation, data display, and conclusion drawing. The results of this study explain the perception of students in a neutral manner based on the phenomena experienced at UINSI Samarinda related to the concept of ethics in the use of AI in learning with the ethical limitations discussed as follows: 1) Absence of data privacy and security issues and their prevention; 2) Plagiarism avoidance that must be done because there is great potential that occurs at the location, and; 3) Responsibilities that are only carried out by some students.